Estimating and examining the costs of inpatient diabetes care in an Irish Public Hospital. Issue 4 (4th December 2021) - Friel, Kathleen M.; Gillespie, Patrick; Coates, Vivien; McCauley, Claire; McCann, Michael; O'Kane, Maurice; McGuigan, Karen; Khamis, Amjed; Manktelow, Matthew
Abstract: Aim: To estimate and examine hospitalisation costs of Type 1 and Type 2 diabetes in an Irish public hospital. Methods: A retrospective audit of hospital inpatient admissions over a 5‐year period was undertaken, and a wide range of admission‐related data were collected for a sample of 7, 548 admissions. Hospitalisations were costed using the diagnosis‐related group methodology. A series of descriptive, univariate and multivariate regression analyses were undertaken. Results: The mean hospitalisation cost for Type 1 diabetes was €4, 027 and for Type 2 diabetes was €5, 026 per admission. Sex, admission type and length of stay were significantly associated with hospitalisation costs for admissions with a primary diagnosis of Type 1 diabetes. Age, admission type, diagnosis status, complications status, discharge destination, length of stay and year were significantly associated with hospitalisation costs for admissions with a primary diagnosis of Type 2 diabetes. Length of stay was associated with higher mean costs, with each additional day increasing Type 1 diabetes costs by €260 ( p = 0.001) and Type 2 diabetes by €216 ( p < 0.001). Unscheduled admissions were associated with significantly lower costs than elective admissions; €1, 578 ( p = 0.035) lower for Type 1 diabetes and €2, 108 ( p < 0.001) lower for Type 2 diabetes. Conclusions: This study presents estimates of the costs of diabetes care in the Irish public hospital system and identifies the factors which influence costs for Type 1 and Type 2 diabetes. These findings may be of interest to patients, the public, researchers and those with influence over diabetes policy and practice in Ireland and internationally.